Hubungan Interaksi Orangtua dan Interaksi Teman Sebaya dengan Perkembangan Moral siswa MAS Babussalam Kabupaten Tapanuli Selatan - Surya Natogar; Abrar Parinduri; Nuraini Nuraini (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the relationship between parents interaction and student self-regulated learning in MAS Babusslam  of South Tapanuli District. This research is a quantitative research with a population of 295 students of MAS Babusslam  of South Tapanuli District. By using the total sampling technique obtained a sample of 170 people. Data collection techniques used three scales, consisting of a scale of parents interaction, peer interaction, moral development. Data analysis techniques using Multiple Regression Analysis. The results showed a significant positive correlation with parents interaction with self-regulated learning r_xy = 0.513 with p = 0.000, coefficient r^2= 0.263. This shows that self-regulated learning is shaped by parents interaction with a contribution of 26.3%. There is a significant positive correlation between peer interaction and moral development, where the coefficient of r_xy = 0.521 with p = 0.000, r^2 = 0.271. This shows that self-regulated learning is formed by peer interaction with a contribution of 27.1%. In addition, based on the results of data analysis, there was a significant relationship between parents interaction and peer interaction with self-regulated learning, where the coefficient of r_xy = 0.724 with p = 0.000 means p <0.050. The determinant coefficient (r^2) of the relationship between parents interaction, peer interaction and the dependent variable of self-regulated learning is r^2 = 0.524. This shows that self-regulated learning is formed by parents interaction and peer interaction with a contribution of 52.4%.